Sistem Informasi Inventarisasi Laboratorium Teknik Informatika Politeknik Kampar - Andri Nofiar Am; Fenty Kurnia Oktorina (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The process of collecting data on the use of equipment and to find out the computer specifications of the Kampar Polytechnic Informatics Engineering laboratory is still done manually. Where to find out the specifications of a computer, the user must turn on the computer first and the technician opens the application to see the specifications of the computer. The solution for this problem is to create an inventory information system for the Informatics Engineering Laboratory of the Kampar Polytechnic. The implementation process carried out in the website version uses the PHP programming language, phpMyAdmin to manage the MySQL database and uses the CodeIgniter 3 Framework, in the desktop and mobile versions using the Java programming language, the php server is used for data management, and the MySQL database for data storage. The results obtained in the form of an inventory information system for the Kampar Polytechnic Informatics Engineering laboratory have been successfully created and can make it easier for users to find out computer specifications quickly, precisely and accurately.